Leukemia Stem Cell Frequency at Diagnosis Correlates With Measurable/Minimal Residual Disease and Impacts Survival in Adult Acute Myeloid Leukemia - Kamel, Azza M.; Elsharkawy, Nahla M.; Kandeel, Eman Z.; Hanafi, Marwa; Samra, Mohammed; Osman, Randa A. (Frontiers in Oncology, 2022)
Acute myeloid leukemia (AML) is a heterogenous disease in which the initiation and maintenance of the malignant clone is blamed on a rare population of leukemia stem cells (LSCs). The persistence of such a malignant population is referred to as measurable/minimal residual disease (MRD). Evaluation of MRD is the gold standard for follow-up of therapy and constitutes an independent prognostic parameter. As LSCs are the main contributor to the persistence of MRD, then MRD should correlate with the bulk of LSCs at the individual case level. MRD is measured at defined time points during therapy. However, LSCs can be evaluated at diagnosis, which ensures the advantage of early prediction of high-risk patients and allows for early therapeutic decisions. Using two simple four-color monoclonal antibody combinations (CD38/CD123/CD34/CD45 and CD90/CD133/CD45/CD33) and the prism function of the Coulter Navios flow cytometer, the frequency of LSC subsets was evaluated in 84 newly diagnosed adult AML patients. For each panel, 16 possible combinations were detected. Our results showed that there was extreme variability in the percentage of the LSC fraction between different cases, as well as at the individual case level. For each LSC subset, the median value was used to divide cases into low and high expressors. LSC subsets that showed an impact on overall survival (OS) and disease-free survival (DFS) included CD123+, CD 123+/CD34-, CD34-/CD38+/CD123+, CD34+/CD38-/CD123+, CD133+, and CD133+/CD33-. On multivariate analysis, only CD123 (p ≤ 0.001, SE = 0.266, HR = 2.8, 95% CI = 1.74.7) and CD133+/CD33- (p = 0.017, SE = 0.263, HR = 1.9, 95% CI = 1.1–3.1) retained their significance for OS. Likewise, only CD34+/CD38-/CD123+ (p ≤ 0.001, HR 2.3, SE: 0.499, 95% CI: 2.4–17.4) and CD133 (p = 0.015, HR 2.3, SE 0.34, 95% CI: 1.2–4.4) retained their statistical significance for DFS. The LSC frequency at diagnosis showed a moderate to strong correlation with MRD status at day 14 and day 28. In conclusion, the level of LSCs at diagnosis correlated with MRD status at day 14 and day 28 in AML patients and had a deleterious impact on OS and DFS. It may be used as an early marker for high-risk patients allowing for early therapeutic decisions.